Future-Proofing Data: Assessing the Feasibility of Post-Quantum Cryptographic Algorithms to Mitigate ‘Harvest Now, Decrypt Later’ Attacks - , Abayomi Titilola Olutimehin; , Sunday Abayomi Joseph; , Adekunbi Justina Ajayi; , Olufunke Cynthia Metibemu; , Adebayo Yusuf Balogun; , Oluwaseun Oladeji Olaniyi (Archives of Current Research International, 2025)
This study evaluates the feasibility of post-quantum cryptographic (PQC) algorithms in mitigating "Harvest Now, Decrypt Later" (HNDL) attacks as quantum computing advances threaten classical encryption. Using datasets from the NIST Post-Quantum Cryptography Project, Deloitte’s PQC Adoption Survey, and IBM & Google Quantum Roadmaps, the study applied statistical modeling, Monte Carlo simulations, and ARIMA forecasting to assess PQC security resilience, adoption readiness, and quantum decryption feasibility. The findings indicate that CRYSTALS-Kyber and CRYSTALS-Dilithium outperform RSA-2048 and ECC-256 in quantum resistance, with attack cost thresholds exceeding 1.91×10101.91 × 10^{10}1.91×1010 compared to 2.24×1082.24 × 10^82.24×108 for RSA-2048. Industry adoption varies, with government PQC implementation at 79%, finance at 67%, and healthcare lagging at 48%. Quantum decryption probability remains negligible until 2029 but rises to 78.6% by 2033. This study addresses the critical challenge of post-quantum cryptographic (PQC) adoption amid growing quantum threats, particularly "Harvest Now, Decrypt Later" (HNDL) attacks. By evaluating PQC security resilience, industry adoption, and quantum decryption feasibility, the findings provide strategic insights for policymakers and cybersecurity experts. Highlighting the vulnerabilities of CRYSTALS-Kyber to side-channel attacks, this research underscores the need for continuous cryptanalysis, hybrid encryption models, and adaptive security frameworks to future-proof data.Organizations must accelerate PQC adoption, integrate hybrid cryptographic models, enforce regulatory policies, and sustain cryptanalysis efforts to ensure long-term security.